Gaya Bahasa Metafora pada Lagu “Ano Hi, Ano Sekai de” Karya Mitei no Hanashi - Sherly; Dhaniar Asmarani (Janaru Saja Jurnal Program Studi Sastra Jepang, 2026)
Abstract In literary works, it is common for readers to encounter metaphors and find it difficult in understanding them. The problem addressed in this study is the limited understanding of the systematic concepts of metaphorical language styles and the components that construct metaphors in literary works, particularly in Japanese song lyrics. This study aims to identify the types of metaphorical language styles and analyzes the metaphor components found in the song “Ano hi, Ano Sekai De” by Mitei no Hanashi. The analysis is based on the theory of metaphorical language styles proposed by Lakoff and Johnson (2003), as well as the metaphor component theory by I. A. Richards and G.N. Leech (1936). This research uses a qualitative approach and descriptive analysis method using the song lyrics as the primary data source. The results of this study reveal the presence of structural, orientational, and ontological metaphors. This research is expected to contribute to the expansion of stylistic studies, particularly in the analysis of metaphors in Japanese song lyrics, and to help readers understand metaphorical meanings in Japanese songs more systematically. Keywords: Language style, Metaphor, Components of Metaphor, Song   Abstrak Dalam sebuah karya sastra, umumnya pembaca akan menemukan metafora dan kesulitan untuk memahaminya. Permasalahan dalam penelitian ini adalah masih kurangnya pemahaman mengenai konsep sistematis jenis gaya bahasa metafora serta komponen pembentuk metafora dalam karya sastra, khususnya pada lirik lagu Jepang. Penelitian ini bertujuan untuk mengidentifikasi jenis gaya bahasa metafora dan menganalisis komponen metafora yang terdapat dalam lagu “Ano hi, Ano Sekai De” karya Mitei no Hanashi. Penelitian ini dianalisis menggunakan kajian jenis gaya bahasa metafora oleh Lakoff dan Johnson (2003), serta kajian komponen gaya bahasa metafora oleh I. A. Richards dan G.N. Leech (1936). Selain itu, penelitian ini menggunakan pendekatan kualitatif dengan metode analisis deskriptif melalui sumber data primer berupa lirik lagu tersebut. Hasil penelitian ini menunjukkan terdapat metafora berjenis struktural, orientasional, dan ontologis. Kontribusi penelitian ini diharapkan dapat memperluas kajian stilistika, khususnya dalam analisis metafora pada lirik lagu Jepang, serta membantu pembaca memahami makna metafora pada lagu Jepang secara lebih sistematis. Kata kunci: Gaya Bahasa, Metafora, Komponen metafora, Lagu